Marketing Strategy on Kepahiang Cahaya Baru Furniture - Amrullah Amrullah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
Formulation of strategy marketing of company of including developing business mission, recognizing opportunity, and threat of eksternal company, specifying internal weakness and strength, specifying long-range objectivity, yielding alternative strategy, and chosen certain strategy be achieved.Target of which wish to be reached in this research is : To know strategy marketing of coffee powder stamp gold stork at company of Meubel Cahaya Baru kepahiang.Research type the used is descriptive of analysis. Method data collecting the used is method field of research by; Interview and Observation.Analysis method which is used in this research is method analysis SWOT (Strengths, Opportunities, Weaknesses, and Threats). This Analysis is relied on logic able to maximize strength and opportunity, but concurrently minimization can weakness and threat.